Correlation between endothelial dysfunction, inflammatory status, oxidative stress and total (nitrite/ nitrate) in subjects with diabetes mellitus type 2 - Reddy, C. Prabhakar; Chiranjeevi, Uday Kumar; N., Chandrasekhar; K., Kiran Kishore; P. V., Kishan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes Mellitus is a systemic metabolic disorder associated with Endothelial dysfunction and increased systemic inflammatory state with oxidative stress leading to increased Cardiovascular risk. This study planned to correlate the level of Endothelial dysfunction with oxidative stress and inflammatory status. Methods: Study was conducted in 60 Diabetes Mellitus subjects of both genders with duration of more than two years. Endothelial dysfunction assessed as Augmentation Pressure and Augmentation Index generated from Radial artery waveforms by tonometer using Spygmocor PWA system. Plasma Total Nitrite/ Nitrate, High sensitive C - Reactive Protein, Malondialdehyde and Glutathione were measured. Results: Out of total 60 Diabetes Mellitus subjects 16 subjects were with Coronary Artery Disease. There was no significant difference in High sensitive C - Reactive Protein, Glutathione, Malondialdehyde and Total Nitrite/ Nitrate between Diabetes Mellitus with Coronary Artery Disease and without Coronary Artery Disease, however significant difference (p=0.02) was observed Augmentation Pressure between Diabetic alone (12.8±5.19 mm of Mercury) and diabetics with Coronary Artery Disease (16.13±33.47 mm of Mercury) and Augmentation Index (p=0.04) between Diabetic alone (29.8±5.68 mm of Mercury) and diabetics with Coronary Artery Disease (40.01±5.74). As endothelial function is age dependent the subjects were divided into three age groups (20-40 years, 40-60 years and more than 60 years). High sensitive C - Reactive Protein, Glutathione, Malondialdehyde, Total Nitrite/ Nitrate and Augmentation Index did not differ in the three age groups while Augmentation Pressure (p=0.0096) showed significant difference between age group 20-40 years (10.59±3.24) and age group more than 60 years (15.83±3.92). Conclusions: There is significant endothelial dysfunction observed in Diabetes Mellitus subjects and Diabetes Mellitus with coronary artery disease showed greater endothelial dyfunction. Thereby concluding that Diabetes Mellitus subjects were at higher risk for development of coronary artery disease and as endothelial dysfunction is an early event, it may have some prognostic value.